Changes to fibrinolysis in patients with systemic lupus erythematosus are associated with endothelial cell damage and inflammation, but not antiphospholipid antibodies. Issue 8 (December 2016) - Dhillon, Parvinderjit K.; Khalafallah, Alhossain A.; Adams, Murray J.
Abstract : We investigated whether changes to fibrinolysis were associated with other manifestations of systemic lupus erythematosus (SLE), including antiphospholipid (APL) antibody status, endothelial damage, and inflammation. Ninety-four patients (36 SLE patients, 58 healthy controls) were recruited from Tasmania, Australia. Circulating levels of plasminogen, α2-antiplasmin, tissue-type plasminogen activator, plasminogen activator inhibitor-1, and thrombin-activatable fibrinolysis inhibitor (TAFI) were measured, as well as APL antibodies (including lupus anticoagulant, anticardiolipin, and antibeta-2 glycoprotein-1 antibodies), soluble E-selectin, and interleukin-6. Whereas there was a significant decrease in plasminogen (patient vs. control; median) (210 vs. 444 ng/ml; P < 0.0001) and increase in α2-antiplasmin (0.53 vs. 0.09 μg/ml; P = 0.0007), there was increased t-PA (0.65 vs. 0.40 ng/ml; P = 0.0001) and decreased TAFI (8.8 vs. 10.0 ng/ml; P = 0.002) in SLE patients compared to healthy controls. Plasminogen was significantly associated with α2-antiplasmin (rho = −0.563, P < 0.001); TAFI (rho = 0.410, P = 0.011); soluble E-selectin (rho = 0.531, P = 0.001); and interleukin-6 (rho = 0.489, P = 0.002) in SLE patients; however, APL antibody status was not associated with any of the markers measured. This study has demonstrated that fibrinolysis is significantly altered in patients with SLE compared to controls, and associated with endothelial cell damage and inflammation, but not APL antibody status.